Edukasi “Pelayanan Lansia Sehat Sejahtera” Implementasi UU No. 13 tahun 1998 Tentang Kesejahteraan Lanjut Usia - Imron Rosadi; Ade Burhan; Ai Astuti; Supiadin Supiadin (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2026)
The  elderly,  or  older  people,  are  individuals  in  the  later  stages  of  life,  usually  aged  60  years  and  above,  and face various challenges that affect their physical, mental and social health. Health-wise, the elderly often suffer from  chronic  diseases  such  as  hypertension,  diabetes  and  heart  disease  that  require  long-term  management. Declines  in  physical  and  cognitive  function,  including  mobility,  muscle  strength,  and  thinking  ability,  are  a natural  part  of  the  aging  process.  In  addition,  older  adults  are  also  prone  to  mental  health  issues,  such  as depression and anxiety, which are often caused by social isolation and loss of loved ones. Socially, many older adults  feel  lonely  and  isolated,  especially  after  losing  a  spouse  or  friend,or  if  they  do  not  have  close  family. Social support from family, friends and the community becomes crucial for their emotional well-being. From an environmental aspect, older people often live in housing that does not suit their needs, such as poor accessibility and unsafe  neighborhoods.  Difficulties  in  accessing  the  health,  social  and  support  services  they  need are  also significant  challenges.  The  care  and  support  provided  to  older  people,  including  regular  health  care  and emotional  and  social  support,  iscrucial  to  improving  their  quality  of  life.  However,  financial  limitations  are often  a  barrier  to  getting  the  necessary  care  and  meeting  basic  needs.  In  addition,  existing  policies  and regulations  sometimes  do  not  adequately  support  the  protection  and  care  of  older  people.  Understanding  the challenges older people face and providing appropriate support is essential to ensure they can lead healthy and dignified lives in old age.